Late effects of early childhood cancer therapy. - Meadows, A. T. (Nature Publishing Group, 1992)
The late effects of cancer treatment in children diagnosed early in life (under 2 years of age) may be compared to those in children who were over 2 years at the time of diagnosis. Such areas as growth and development (e.g., intellectual and sexual), vital organ function and risk for second cancer are of particular interest. This report reviews late occurring morbidity which was studied in approximately 400 survivors of childhood cancer, 93 of whom were under 2 years of age at diagnosis. The most commonly reported late effect was musculoskeletal in radiation treated patients. More severe cognitive deficits were seen among both age groups cranially irradiated for leukaemia prophylaxis with 24 Gy compared to 18 Gy. Second cancers developed equally between the two age groups. Predisposing factors and/or prior therapy may produce second cancers. There are inherent problems in assessing the outcomes of very young children treated for cancer. Improved survival has only been evident during the last 15 years, a period too short to appreciate many of the end points of interest in adult life. Such patients require a necessarily long follow-up period but this will prove informative in the future as more institutions initiate procedures for extended surveillance.